Synthesis and X-Ray Diffraction of a Ternary Plumbum Complex - Bi, Jian-Hong; Dong, Hua-Ze; Wang, Yu-Miang (Asian Journal of Chemistry, 2013)
A new ternary plumbum complex [Pb(phen)2(NO3)2] (phen = 1,10-phenanthroline) has been synthesized and characterized by IR spectra and single-crystal X-ray diffraction. The crystal belongs to monoclinic crystal system and has space group P2(1)/n with unit cell parameters: a =16.7304(15) Å, b = 7.7529(7)Å, c = 18.1308(17) Å, a = 90º, b = 98.2170(10)º, g = 90º, V = 2327.6(4) Å3, Z = 4, Mr = 691.62, Dc = 1.974 Mg/cm3, μ = 7.303 mm-1, F(000) =1328, T = 298(2) K, R = 0.0306, wR = 0.0574 for 11276 reflections with I > 2s(I). In terms of the crystal structure, Pb(II) ion is eight-coordinated with four nitrogen atoms of the two phen ligands and four oxygen atoms of the two nitrate radical anions.